The Effect of Politics and Humanity Issue on Tourism Sector Development in Myanmar - Y.N.P, Aberrant Pratama; Qonita, Khansa; N., Tri Sandy (Universitas Sebelas Maret, 2020)
Tourism is one of the sectors that can support development of a country by contributing in foreign exchange. In order to attract tourists from around the world, a country must open up to the international order. Myanmar is one of many countries opening itself up in order to promote the country among tourists. A lot of infrastructure developments, especially in the field of tourism, were done in Myanmar, such as hotels and recreation areas. But the Myanmar government uses their authority to force men who take military services to do some labor jobs. Hence, this issue was exposed and got a lot of criticisms from international society, some countries even boycotting Myanmar’s tourism, as well as Myanmar’s recent security and humanity issue regarding violence to Rohingya people that was done by Myanmar’s military. Apparently, this issue aggravates Myanmar’s image in a lot of tourists’ perspectives. So many tourists cancelled their holiday plan in Myanmar because of this Rohingya issue. In this journal, there will be a discussion about how humanity issues could affect the image of a country which will later affect the tourism field as well.